2023
DOI: 10.21203/rs.3.rs-3099291/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human-AI Collaboration to Identify Literature for Evidence Synthesis

Abstract: Systematic approaches to evidence synthesis can improve the rigour, transparency, and replicability of a traditional literature review. However, these systematic approaches are time and resource intensive. We evaluate the ability of OpenAI’s ChatGPT to undertake two initial stages of evidence syntheses (searching peer-reviewed literature and screening for relevance) and develop a novel collaborative framework to leverage the best of both human and AI intelligence. Using a scoping review of community-based fish… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…In the medical sciences, where evidence synthesis methods are well developed and widely used, recent studies demonstrate the promising role that AI tools can play in carrying out rapid and extensive literature reviews [8,12]. At the same time, there is also discourse around potential challenges and limitations regarding the usefulness of these platforms [7,[13][14][15].…”
Section: Artificial Intelligence Is Revolutionizing Conservation Sciencementioning
confidence: 99%
See 4 more Smart Citations
“…In the medical sciences, where evidence synthesis methods are well developed and widely used, recent studies demonstrate the promising role that AI tools can play in carrying out rapid and extensive literature reviews [8,12]. At the same time, there is also discourse around potential challenges and limitations regarding the usefulness of these platforms [7,[13][14][15].…”
Section: Artificial Intelligence Is Revolutionizing Conservation Sciencementioning
confidence: 99%
“…Researchers have shown that the use of LLM tools can substantially shorten, by as much as six-fold, the time spent screening relevant research ( [8,12,13], Box 2). LLMs could also be applied to (meta)data extraction from relevant studies and summarize a collection of articles more efficiently [8,16,17].…”
Section: Speedmentioning
confidence: 99%
See 3 more Smart Citations